CREATIVE V. PURPOSIVE SPORTS: NEED FOR RECOGNIZING SPORTS PERSONS AS PERFORMERSUNDER COPYRIGHT LAW - et. al., Vaishnavi Venkatesan (International Journal of Modern Agriculture, 2021)
The sports industry is a multi-billion-dollar global market in terms of revenue and employment. Gone are the days when cricket was a synonym to sports in India. Other sports including aesthetic sports are re-writing its growth abundantly. Sports persons are the vital connecting link between a game in this inordinately emerging industry and it is transferred to the public in general. Despite the fact players in certain sports like cricket, football or hockey operate within certain boundaries owing to the restrictive rule bound nature of these games, as a contrast to ice skating, gymnastics and artistic swimming which are inherently creative, there exist certain sports persons who ‘contribute creatively’ in a manner which goes beyond the rules of the game. The creativity of sports persons within a game or after its conclusion is manifested in the form of distinct ‘sports moves’ or ‘celebratory dances’. These movements which operate as ‘signature moves’ of such players are nothing but an extension of the athlete’s personality and charisma. These add to their marketability, professional net worth and reputation considerably. For instance, during IPL matches many players have come up with their own style of rejoicing over wickets or runs, for example Darren Sammy, Chris Gayle ,the unique pose Usain Bolt gives on winning a race or MS Dhoni’s helicopter shot. This paper seeks to examine the Performance Rights of sports persons in-depth. It analyses the meaning of the terms ‘performance’ and ‘performers’ comprehensively and proposes the extension of performers rights under the copyright law to sportspersons who are able to meet the ‘creativity’ and ‘originality’ threshold to contribute effectively. However, keeping in mind, the inherent competitive nature of sports and the doctrine of fair use, claiming remuneration in the form of economic rights for such creative contributions might contravene the said principles. Accordingly, the author proposes recognizing these sports persons contributing creatively as ‘performers’ and meriting them with moral rights to protect their work from distortion or modification and to safeguard their reputation with an objective of promoting creativity in the domain of sports.